Scenario Planning of Electricity Needs In Indonesia for The Next Ten Years - Wijayanto, Hari Dwi; Sunitiyoso, Yos (SBM ITB, 2019)
Abstract. Indonesia as the largest archipelago in the world, has its own challenges in energy supply infrastructure compared with continental countries. According to data from Directorate General of Electricity (2018), the electrification ratio Indonesia until the end of 2017 just around 95,37%. Even more, there are two provinces that have electrification ratio below 70% (NTT 59,85% and Papua 61,94%). Compared with other ASEAN countries, Indonesia's national electrification ratio is still low. The electrification ratio of Thailand and Singapore already 100%. Malaysia and Brunei Darussalam have 99% electrification ratio and Vietnam with electrification ratio reaching 98%. Therefore, at this time the Government seeks to achieve electrification ratio 99,90% in 2019. For that reason, the government is trying to increase electrification ratio by 35.000 MW program. But to realize this, the government must face high uncertainty of the future. So it needed scenario planning approach to prevent unwanted conditions. The purpose of this study is not only to provide an overview of the future situation in the electricity industry and all aspects that may impact on changes in the electricity sector, but also being able to transform from one scenario to another scenario with a better future. There are two main uncertainty factors with the greatest impact that is the level of economic growth and security of primary energy supply to power plant. Then these two factors of uncertainty are used as axis to create four quadrants containing four scenarios that will occur. The four scenarios are Alert Industry, Full of Light Industry, Climbdown Industry, and Blackout Industry.Keywords: Scenario Planning, Electrification Ratio, 35.000 MW Program, Economic Growth, Security of Primary Energy Supply.Abstrak. Indonesia sebagai negara kepulauan terbesar di dunia, memiliki tantangan tersendiri dalam infrastruktur pasokan energi dibandingkan dengan negara kontinental. Menurut data dari Direktorat Jenderal Ketenagalistrikan (2018), rasio elektrifikasi Indonesia hingga akhir 2017 hanya sekitar 95,37%. Terlebih lagi, masih ada dua provinsi dengan rasio elektrifikasi di bawah 70% (NTT 59,85% dan Papua 61,94%). Dibandingkan dengan negara-negara ASEAN lainnya, rasio elektrifikasi nasional Indonesia masih rendah. Rasio elektrifikasi Thailand dan Singapura sudah 100%. Malaysia dan Brunei Darussalam memiliki rasio elektrifikasi 99% dan Vietnam dengan rasio elektrifikasi mencapai 98%. Sehingga saat ini Pemerintah berupaya mencapai rasio elektrifikasi 99,90% pada 2019. Oleh karena itu, pemerintah berupaya meningkatkan rasio elektrifikasi melalui program 35.000 MW. Tapi untuk merealisasikan hal ini, pemerintah harus menghadapi ketidakpastian yang tinggi di masa depan. Sehingga dibutuhkan metode perencanaan skenario untuk mencegah kondisi yang tidak diinginkan. Tujuan dari penelitian ini adalah tidak hanya untuk memberikan gambaran umum situasi masa depan di industri ketenagalistrikan dan semua aspek yang berdampak pada perubahan sektor ketenagalistrikan, namun juga dapat mengubah dari satu skenario ke skenario lain dengan masa depan yang lebih baik. Ada dua faktor ketidakpastian utama dengan dampak terbesar yaitu tingkat pertumbuhan ekonomi dan keamanan pasokan energi primer terhadap pembangkit listrik. Kemudian kedua faktor ketidakpastian ini digunakan sebagai sumbu untuk membuat empat kuadran yang berisi empat skenario yang akan terjadi. Keempat skenario tersebut adalah Alert Industry, Full of Light Industry, Climbdown Industry, dan Blackout Industry.Kata kunci: Perencanaan Skenario, Rasio Elektrifikasi, Program 35.000 MW, Pertumbuhan Ekonomi, Keamanan Pasokan Energi Primer.